Amplitud de distribución eritrocitaria como factor asociado a sepsis temprana en neonatos prematuros del Hospital III Iquitos, 2020-2023 - Acuña Perez, Patrick Johnnattan (2025)
Early-onset sepsis is a cause of morbidity and mortality in premature newborns (NB). Depending on its appearance, it can be divided: early neonatal sepsis (NS), which develops between the first 72 hours, and late NS, after 72 hours (1). At a global level, efforts are being made to reduce neonatal mortality rates, currently around 43 per 1000 live births, with a special focus on developing countries (2) due to the limitations they may present with respect to diagnosis. In this context, it is proposed to explore the amplitude or width of erythrocyte distribution (RDW) as a potential marker of early NS, since it has demonstrated increases in infectious symptoms in neonates, especially in those who die from sepsis. RDW is a parameter included in the routine complete blood count (2). This means that its measurement would not require advanced equipment or technologies, making it especially suitable for resource limited settings, such as neonatal hospitals in regions such as Iquitos. This is important in the case of early neonatal sepsis, where early detection can make a difference in initiating treatment and preventing serious complications (3). Taken together, the use of ADE as a diagnostic marker of early NS in preterm neonates is justified by its accessibility, its association with the inflammatory response, and its potential to positively impact clinical care.